2020
DOI: 10.26832/24566632.2020.0501010
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary toxicity assessment of chromium (Cr) and lead (Pb) on terrestrial snail (Helix aspersa)

Abstract: Chromium and lead are among the major toxicants that have their own environmental concerns and are very harmful for living organisms even in small concentrations. The present study is performed to evaluate the acute toxicity potential of chromium and lead on terrestrial garden snail (Helix aspersa) at different concentration ranges from 1.0 mg/L to 20 mg/L at different exposure time. In determining acute toxicity, LC 50 values after 24, 48, 72 and 96 h for both the metals were determined by probit statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Also, the LC 50 result revealed that the Itel phone battery was more toxic and lethal to L. flammea population than the Gionee phone battery. Previous research by Dhiman [18] reported the LC 50 for chromium was 4.027 mg/L for 96 h period of exposure while lead LC 50 values was 1.352 mg/L for 96 h period of exposure, respectively on terrestrial snail (Helix aspersa).…”
Section: Discussionmentioning
confidence: 90%
“…Also, the LC 50 result revealed that the Itel phone battery was more toxic and lethal to L. flammea population than the Gionee phone battery. Previous research by Dhiman [18] reported the LC 50 for chromium was 4.027 mg/L for 96 h period of exposure while lead LC 50 values was 1.352 mg/L for 96 h period of exposure, respectively on terrestrial snail (Helix aspersa).…”
Section: Discussionmentioning
confidence: 90%
“…At the examined sites in the Upper Rhine, which were partly close to industry locations, chromium exposure was connected to pathologic alterations in male reproductive organs of Danubian T. fluviatilis . Playing an important role in environmental pollution in general due to its wide use in many industries like steel welding, mining, or coating applications (Dhiman 2020 ; Sivakumar et al 2014 ), chromium is one of the more toxic metals for biota. Its toxicity cannot be reduced by protein binding and accumulation within organisms to reduce its bioavailability, therefore it needs to be completely detoxified or excreted (Rainbow 2002 ; Sivakumar et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, especially hexavalent compounds of chromium (Cr 6+ ) have in many laboratory studies shown to be highly toxic for animals, leading to negative effects of chromium exposure on male reproductive systems including morphological damage, altered testicular biochemistry or decreases in testis proteins (summarised by Campbell et al 2009 ). Toxicity studies using the terrestrial snail Helix aspersa demonstrated acute chromium exposure to cause increased mortality and electrolyte disturbance in test animals (24h-LC 50 15.13 mg/L, Dhiman 2020 ). The findings in our study indicate its toxicity to be of a relevance for aquatic snails as well.…”
Section: Discussionmentioning
confidence: 99%
“…In: Advances in Environmental Pollution Management Varun Dhiman et al (2020) in Environmental Science, 7: 66. Shakoor, M.B., Ali, S., Rizwan, M., Abbas, F., Bibi, I., Riaz, M. and Rinklebe, J.…”
Section: Conflict Of Interestmentioning
confidence: 99%